Gestión de Manejo del Recurso Hídrico para consumo humano en el Barrio San José de Pichul, Parroquia Eloy Alfaro, Cantón Latacunga, Provincia de Cotopaxi, periodo 2018 - Flores Cruz, Maritza Elizabeth (2019)
Water is one of the key resources in order to survive, mainly because it is naturally. Passing time, the anthropogenic activities have altered their condition, which seriously affects the aquatic life that can be found and various ways of utilization of this resource use. This research was carried out with the purpose to optimize the water quality of a natural shed that caters to the people of the San Jose de Pichul. It has been done physical, chemical and microbiological characterization with water samples taken at catchment tank, regulation tank and address of the sector, with the results of a specialized laboratory determined the parameters that were outside allowable limit of Ecuadorian legislation TULSMA, as Total hardness, biochemical oxygen demand (BOD) and chemical oxygen demand (COD). Water resources management were based on a set of efficient processes to treat water as the cooling system submersible type Jet which is a complement in coagulation and flocculation process is also a horizontal flow flocculator, a lamellar sedimentation tank and a system of rapid sand filtration. The research contributes to ensuring the quality of life of San José neighborhood as well as the life of the people of three nearby neighborhoods who is supplying this service, taking into account that use of water for human consumption and domestic purposes.